Cyclooxygenase‐2 is acutely induced by CCAAT/enhancer‐binding protein β to produce prostaglandin E 2 and F 2α following gonadotropin stimulation in Leydig cells. Issue 7 (13th May 2019) - Yazawa, Takashi; Imamichi, Yoshitaka; Yuhki, Koh‐ichi; Uwada, Junsuke; Mikami, Daisuke; Shimada, Masayuki; Miyamoto, Kaoru; Kitano, Takeshi; Takahashi, Satoru; Sekiguchi, Toshio; Suzuki, Nobuo; Rafiqul Islam Khan, Md.; et al.
Abstract: Cyclooxygenase 2 (COX‐2) is an inducible rate‐limiting enzyme for prostanoid production. Because COX‐2 represents one of the inducible genes in mouse mesenchymal stem cells upon differentiation into Leydig cells, we investigated COX‐2 expression and production of prostaglandin (PG) in Leydig cells. Although COX‐2 was undetectable in mouse testis, it was transiently induced in Leydig cells by human chorionic gonadotropin (hCG) administration. Consistent with the finding that Leydig cells expressed aldo‐keto reductase 1B7 (PGF synthase) and PGE synthase 2, induction of COX‐2 by hCG caused a marked increase in testicular PGF2α and PGE2 levels. Using mouse Leydig cell tumor‐derived MA‐10 cells as a model, it was indicated by reporter assays and electron mobility shift assays that transcription of the COX‐2 gene was activated by CCAAT/enhancer‐binding protein β (C/EBPβ) with cAMP‐stimulation. C/EBPβ expression was induced by cAMP‐stimulation, whereas expression of C/EBP homolog protein (CHOP) was robustly downregulated. Transfection of CHOP expression plasmid inhibited cAMP‐induced COX‐2 promoter activity. In addition, CHOP reduced constitutive COX‐2 expression in other mouse Leydig cell tumor‐derived TM3 cells. These results indicate that COX‐2 is induced in Leydig cells by activation of C/EBPβ via reduction of CHOP expression upon gonadotropin‐stimulation to produce PGF2α and PGE2 . Abstract : In testis, cyclooxygenase 2 is transiently induced by human chorionic gonadotropin in Leydig cells. Testicular concentrations of PGF2ɑ and PGE2 are markedly increased at this time.